Avaliação dos efeitos de impactos antrópicos em ambientes aquáticos de Manaus (Amazonas, Brasil) através da comunidade de invertebrados e da decomposição foliar. - Martins, Renato Tavares (Instituto Nacional de Pesquisas da Amazônia - INPA, 2013)
This thesis evaluated the effects of different human impacts (deforestation, input of domestic sewage, increases of atmospheric temperature and CO2) on invertebrates and leaf breakdown in aquatic environments in Manaus, Amazonas state, Brazil. Chapter 1 reevaluated the environmental conditions of 40 urban streams that had been studied previously in 2003. We also evaluated the variability of the invertebrate community between 2003 and 2010. Richness and rarefied richness were negatively influenced by domestic sewage input and by deforestation. The variability of invertebrate communities between 2003 and 2010 was high and did not differ between the reference and impacted streams. High variability in the invertebrate community can result in incorrect evaluations of the quality of aquatic environments. Chapter 2 evaluated the direct and indirect effects of environmental and biological factors on the leaf breakdown of Coussapoa trinervia (Cecropiaceae) e Mabea speciosa (Euphorbiaceae) in 42 streams in Manaus. Fungal biomass had a direct positive effect on leaf breakdown in both species. In M. speciosa (softer leaf tissues), shredder biomass was the most important factor for leaf breakdown. Urbanization had an indirect negative effect on leaf breakdown. The present study provides evidence that urbanization can decrease leaf breakdown rates in streams, mainly through negative effects on the fungal and shredder biomasses. In Chapter 3, the relationship between size (body and case dimensions) and the biomass of Phylloicus elektoros was analyzed using linear, exponential and power regressions. We also evaluated the predictions of our models and of the models developed for Phylloicus sp. from southeastern Brazil. The predictive power of our models was evaluated using cross-validation. We measured four body dimensions (head capsule width, interocular distance, body and pronotum length) of 152 larvae and two case dimensions (width and length) of 45 cases. Case width had the best fit with biomass in all model classes. Body length was the body dimension that provided the best prediction of biomass. The power model provided the best fit between size (body and case dimensions) and biomass. We observed a good fit between body and case dimensions and biomass, but the predictive power of the models was low (~ 40%). Predicted biomasses obtained using models proposed in the literature were 75% lower than the observed values. We do not recommend the use of models proposed in the literature to predict the biomasses of organisms from different regions. Chapter 4 evaluated the effects of temperature and CO2 increases and nutritional quality of leaves of two plant species (Eperua glabriflora [Fabaceae] e Goupia glabra [Celastraceae]) on consumption, growth and survival rates of Phylloicus elektoros. The experiment was conducted in microcosms that simulate real-time temperature and CO2 in the city of Manaus. The microcosm is composed of four rooms; the control condition represents the current values of temperature and CO2, and the other three rooms have conditions different from the control condition, the most extreme condition representing an increase of ~ 4.5 °C in temperature and ~ 870 ppm in CO2. Consumption and survival rates of P. elektoros were significantly lower with increased temperature and CO2. However, only the consumption rate differed between the two plants species, with consumption being higher in G. glabra. Growth rate did not differ among treatments. The temperature and CO2 increases tested in this study may result in large changes in organic matter decomposition and in food chains in Amazon streams, mainly through decrease in consumption and survival of shredders.
Keywords: Insetos aquáticos; Invertebrados aquáticos; Phylloicus elektoros